Effect of Addition of Gypsum Powder on Clay by Direct Shear Pengujian Testing - Josua Gilang Pang’ Raran; Irwan Lie Keng Wong; Ika Apriyani (Paulus Civil Engineering Journal, 2022)
Clay soil is a type of cohesive soil that has low shear strength but high compressibility. The purpose of the study was to determine the physical properties of soil originating from Rantebua Village, Rantebua District, North Toraja Regency, and to determine the effect of adding gypsum to soil originating from Rantebua Village, Rantebua District, north Toraja Regency by direct shear testing. The research method includes testing the phy properties of the soil and mechanical testing on direct shear. The result of the direct shear test that has been obtained shows that each soil sample mixed with gypsum at a composition 12%, 20%, and 28% has an increase in value (c) and value (ϕ). According to the USCS, it is classified as a fine-grained soil type with low to moderate plasticity, then for the result of the direct shear test in the presence of a mixture of gypsum into four soil samples, it can have an increasing effect on the value of (c) and value (ϕ) so that the bearing capacity of the soil becomes better than the soil condition before it was mixed with gypsum.